EVALUATION OF THE ACHIEVEMENT OF MOTOR VEHICLE TAX TARGETS IN ONE-STOP ADMINISTRATION SERVICES OFFICE CIKANDE SERANG BANTEN - Aggraeni, Feni; Pratiwi, Esti Utami; Fazri, Edward; Muttaqin, Galih Fajar (Review of Accounting and Taxation, 2024)
Purpose - This study aims to determine and analyze how variance between the target and the realization of motor vehicle tax revenue Design/methodology/approach - This research approach is descriptive by using data types quantitative, this study was conducted with data received from the Office SAMSAT Kabupaten Serang in the form of data on the number of targets and tax realization Motorized Vehicles so as to provide a fairly clear picture of analyze and compare with existing theory. Research data that carried out in the form of primary data and secondary data. Data analysis techniques used in the form of quantitative descriptive analysis techniques. Finding - The results of the study show that seen from the realization of tax revenue Motor Vehicles for 2015-2019 are still below the targets set, this shows that the performance is carried out by SAMSAT Kabupaten Serang Regency in collecting motor vehicle tax not optimal. Motor vehicle tax revenue is revenue which has the greatest contribution in increasing Regional Original Revenue (PAD). Lack of awareness of taxpayers to report tax objects his motorized vehicle. In this case the taxpayer also tends to delay payment or tend to avoid payment. Originality -